Essence, Alienation and Animal Liberation: Toward a Humanism for Non-Humans. Issue 3 (3rd July 2022) - Fish, Kenneth
ABSTRACT: While Marx's political economy has proven valuable for understanding the animal-industrial complex, there is widespread suspicion that his humanism is incompatible with the goals of critical animal studies. Setting aside the question of what Marx really meant in his rather limited discussions of animals, the purpose of this paper is to distinguish between two forms of humanism in the Marxian tradition and locate the conceptual space occupied by animals in each. Drawing on Lucien Seve's distinction between speculative and scientific humanisms, I argue that, while the former does indeed render animal suffering invisible, the latter does not, and in fact provides valuable conceptual tools for critical animal studies to employ. I contrast these two forms of humanism through the central questions of essence, alienation, and liberation, and explore the implications of these contrasts for theorizing animals. Since these forms of humanism are often found intertwined within a single theorist's work—Marx's included—I construct them in relative abstraction from their manifestation in any particular theorist or strain of Marxism in the hope that doing so will bring their very different consequences for critical animal studies into relief.